Iraq Economic Monitor, Fall 2018 : Toward Reconstruction, Economic Recovery and Fostering Social Cohesion - World Bank Group (World Bank, Washington, DC, 2018)
Iraq’s overall security situation has notably improved after the defeat of ISIS, but significant challenges lie ahead. Iraq has witnessed major political and security transitions in 2017 when Prime Minister Al-Abadi announced in December the victory over ISIS after a war that lasted three years. The defeat of ISIS in Iraq left the government with the daunting tasks of rebuilding the country’s infrastructure, reconstruction of liberated areas, establishing security and stability,and providing services for the return of the displaced persons. On May 12, 2018 Iraq voted in parliamentary elections that delivered a win for a political bloc led by Moqtada al-Sadr, while PM Al-Abadi’s bloc, once seen as front runner, came in third. The ballots have been recounted after allegations of fraud and completed on August 8th without major change. On September 15th, Iraq’s parliament elected lawmaker Mohammed al-Halbousi as speaker, marking a major step towards establishing a new government. On October 2nd, Iraq’s parliament elected as president Barham Salih,who immediately named Adel Abdul Mahdi Prime Minister-designate, ending months of deadlock afterthe national election in May.